Profile of Technological Pedagogical Content Knowledge (TPACK) on Pre-Service Teachers in Higher Education - Krisnaresanti, Aldila; Ahman, Eeng; Disman, Disman (Universitas Negeri Surabaya, 2023)
This study aims to determine the Technological Pedagogical Content Knowledge (TPACK) profile of pre-service teachers at the Economics Education Study Program at Universitas Jenderal Soedirman. This study used quantitative method with a survey research design. The sample of population were 111 respondents from 3rd, 5th, and 7th-semester. To measure TPACK, 50 statements were formulated based on the indicators of each TPACK component, categorized as valid and reliable. Data were analyzed using descriptive statistics. The research results showed that the seven components of TPACK were categorized as good, two components are more prominent, namely Technological Knowledge (TK) and Technological Content Knowledge (TCK), while the lowest component was Content Knowledge (CK). These results suggest that during lectures, it's important to emphasize both mastering the material and integrating technology into learning.